Fructose and Non-Alcoholic Steatohepatitis - Roeb, Elke; Weiskirchen, Ralf (Frontiers in Pharmacology, 2021)
Background: The excessive consumption of free sugars is mainly responsible for the high prevalence of obesity and metabolic syndrome in industrialized countries. More and more studies indicate that fructose is involved in the pathophysiology and also in the degree of disease of non-alcoholic fatty liver disease (NAFLD). In epidemiologic studies, energy-adjusted higher fructose consumption correlates with NAFLD in overweight adults. In addition to glucose, fructose, as an equivalent component of conventional household sugar, appears to have negative metabolic effects in particular due to its exclusive hepatic metabolism. Liver-related mortality is strictly associated with the degree of fibrosis, whereas the most common cause of death in patients suffering from NAFLD and non-alcoholic steatohepatitis (NASH) are still cardiovascular diseases. In this review article, we have summarized the current state of knowledge regarding a relationship between fructose consumption, liver fibrosis and life expectancy in NASH. Method: Selective literature search in PubMed using the keywords ‘non-alcoholic fatty liver’, ‘fructose’, and ‘fibrosis’ was conducted. Results: The rate of overweight and obesity is significantly higher in both, adult and pediatric NASH patients. The consumption of free sugars is currently three times the maximum recommended amount of 10% of the energy intake. The current literature shows weight gain, negative effects on fat and carbohydrate metabolism and NASH with hypercaloric intake of fructose. Conclusions: Excessive fructose consumption is associated with negative health consequences. Whether this is due to an excess of energy or the particular metabolism of fructose remains open with the current study situation. The urgently needed reduction in sugar consumption could be achieved through a combination of binding nutritional policy measures including taxation of sugary soft drinks. Previous studies suggest that diet-related fructose intake exceeding the amount contained in vegetables and fruits lead to an increase of hepatic lipogenesis. Thus, further studies to clarify the protective contribution of low-fructose intake to positively influence NAFLD in industrial population are urgently required.